A Study on Heat Generation of Lithium-Ion Battery Used in Electric Vehicles by Simulation and Experiment - Selvararajoo K.; Wanatasanappan V.V.; Luon N.Y. (Springer Science and Business Media Deutschland GmbH, 2024)
Lithium-ion battery is commonly used for electric vehicles because it has a good lifespan and has low discharge rate. However, the LIB easily gets heated up gradually as it discharges. The rise in battery temperature is a major concern that needs to be focused on due to the safety aspect. Therefore, the thermal behaviour of LIB is simulated and analysed in this study. The equivalent circuit of the Panasonic 18,650 LIB cell is designed in MATLAB using SIMULINK. Then, the battery system is run at an ambient temperature of 25C to simulate the heat production of the charging and discharging process at different discharge rates of 0.5C, 1C and 3C. On the other hand, an experiment with a battery system was conducted to check the temperature rise at the same current rate. The temperature rise graph against the state of charge (SOC) for charging and depth of discharge (DOD) for discharging are obtained at 0.5C, 1C and 3C by both simulation and experiment, and thermal behaviour is analysed. In conclusion, heat generation during battery discharging is higher than the charging process, particularly when conducting the experiment. Overall, both charging and discharging the temperature rise are directly proportional to the SOC and DOD, respectively. 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.